Синтез управління стабілізацією геостаціонарного супутника у точці стояння - Волосов, В.В.; Шевченко, В.М. (Проблемы управления и информатики, 2022)
Розроблено методи та алгоритми балістичного забезпечення управління стабілізацією довготи точки стояння геостаціонарного супутника (ГСС). Еволюція поточних координат ГСС моделювалася диференціальними рівняннями руху матеріальної точки у центральному гравітаційному полі з урахуванням обмежених структурно-параметричних збурень відомої інтенсивності, викликаних загальним впливом Сонця, Місяця, відмінністю гравітаційного поля Землі від центрального тощо. The methods and algorithms for ballistic support of control in the stabilization of the longitude of a geostationary satellite (GSS) at the parking position have been developed. The evolution of the current coordinates of the GSS was modeled by differential equations of motion of a material point in the central gravitational field, taking into account limited structural-parameter disturbances of known intensity, caused by the overall influence of the Sun, the Moon, and the difference in the Earth's gravitational field from the central one, etc. The specific mathematical modeling of these disturbances was not considered; only their general boundedness by norm was used.